Observation of the Ωð2012Þ baryon at the LHC - Acharya, S.; Acharya, S.; Agarwal, A.; Aglieri Rinella, G.; Aglietta, L.; Agnello, M.; Agrawal, N.; Ahammed, Z.; Ahmad, S.; Ahn, S.U.; Ahuja, I.; Akindinov, A.; et al. (American Physical Society, 2025)
A signal consistent with the Ω ( 2012 ) baryon has been observed with a significance of 15 σ in pp collisions at s = 13 TeV at the LHC. In this paper, the analysis technique is described and measurements of the mass and width of the Ω ( 2012 ) are reported, along with the first measurement of its transverse-momentum spectrum and yield. This paper corroborates the observation by the Belle Collaboration of this excited Ω state and the observation that the Ω ( 2012 ) has a rather narrow width for a strongly decaying resonance. The yield measurement is combined with a statistical thermal model calculation of strange baryon yield ratios to obtain estimates of the Ω ( 2012 ) − → Ξ K ¯ branching ratios. These results will improve our understanding of the internal structure and mass spectrum of excited baryon states and serve as a baseline for searches regarding modifications of these properties in high-temperature media.
Keywords: Baryon; Large Hadron Collider; Excited state; Branching fraction; Yield (engineering); Spectrum (functional analysis); Thermal; https://purl.org/pe-repo/ocde/ford#1.03.00